2017
DOI: 10.1002/2016jd026246
|View full text |Cite
|
Sign up to set email alerts
|

Sources and formation processes of water‐soluble dicarboxylic acids, ω‐oxocarboxylic acids, α‐dicarbonyls, and major ions in summer aerosols from eastern central India

Abstract: The sources and formation processes of dicarboxylic acids are still under investigation. Size‐segregated aerosol (nine‐size) samples collected in the urban site (Raipur: 21.2°N and 82.3°E) in eastern central India during summer of 2013 were measured for water‐soluble diacids (C2‐C12), ω‐oxoacids (ωC2‐ωC9), α‐dicarbonyls (C2‐C3), and inorganic ions to better understand their sources and formation processes. Diacids showed the predominance of oxalic acid (C2), whereas ω‐oxoacids showed the predominance of glyoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 110 publications
4
21
0
Order By: Relevance
“…Tai are largely derived from O 3 and OH radical oxidation of BVOCs such as isoprene and α-pinene, while the nighttime oxalic acid and related SOA might be mostly produced by NO 3 radicals and other oxidizing agents such as H 2 O 2 (Claeys et al, 2004;Herrmann et al, 1999). In addition, the titration of O 3 by the residual NO in the nighttime atmosphere could also be responsible for the lack of correlation between BSOA tracers and O 3 (Edwards et al, 2017).…”
Section: Effects Of Temperature Relative Humidity and O 3 Concentratmentioning
confidence: 99%
“…Tai are largely derived from O 3 and OH radical oxidation of BVOCs such as isoprene and α-pinene, while the nighttime oxalic acid and related SOA might be mostly produced by NO 3 radicals and other oxidizing agents such as H 2 O 2 (Claeys et al, 2004;Herrmann et al, 1999). In addition, the titration of O 3 by the residual NO in the nighttime atmosphere could also be responsible for the lack of correlation between BSOA tracers and O 3 (Edwards et al, 2017).…”
Section: Effects Of Temperature Relative Humidity and O 3 Concentratmentioning
confidence: 99%
“…On the other hand, more LWC would lead to increased pH due to dilution. For example, and Duporte et al (2016) found that OS formation decreased with higher RH, which was attributed to increased pH as a result of higher LWC (Duporte et al, 2016;Riva et al, 2016c).…”
Section: Introductionmentioning
confidence: 99%
“…(iv) Although still limited in their ability to provide direct proof, reports of size-resolved field measurements may miss out on the full story of an aqueous signature if only the submicrometer size range (e.g., droplet mode) is examined, as aqueous processing can influence the composition of aerosol in the coarse mode (e.g., Deshmukh et al, 2017).…”
Section: Caution In Characterizing Air Near Clouds To Detect the Cloumentioning
confidence: 99%